2012
DOI: 10.1111/cmi.12036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dihydropyrimidine dehydrogenase as a virulence factor essential for the survival ofEntamoeba histolyticain glucose-poor environments

Abstract: SummaryAdaptation to nutritional changes is a key feature for successful survival of a pathogen within its host. The protozoan parasite Entamoeba histolytica normally colonizes the human colon and in rare occasions, this parasite spread to distant organs, such as the liver. E. histolytica obtains most of its energy from the fermentation of glucose into ethanol. In this study, we were intrigued to know how this parasite reacts to changes in glucose availability and we addressed this issue by performing a DNA mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…We and others have previously reported on the parasite’s ability to adapt to various stresses, such as glucose starvation11, serum starvation40 or treatment with metronidazole41. In this report, we inform on the ability of E. histolytica to adapt to NS.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…We and others have previously reported on the parasite’s ability to adapt to various stresses, such as glucose starvation11, serum starvation40 or treatment with metronidazole41. In this report, we inform on the ability of E. histolytica to adapt to NS.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, we completed a high-throughput proteomic analysis of S-nitrosylated (SNO) proteins in NO-exposed E. histolytica using resin-assisted capture of SNO proteins (SNO-RAC)3, and found that SNO proteins are involved in glycolysis, translation, protein transport, and virulence. It has been reported that E. histolytica can adapt to various stresses910111213. Nevertheless, information on the ability of the parasite to adapt to progressive increases in the intestinal NO concentration, which may occur in patients with inflammation of the large intestine1 or during the establishment of amebiasis14, is lacking.…”
mentioning
confidence: 99%
“…The parasite has two stages in its life cycle: the infective cyst and the invasive trophozoite. In the host, the parasite is exposed to various environmental challenges and is capable of adapting to the demands of its surrounding environment, such as extreme changes in the glucose concentration and the oxidative and nitrosative attacks of the host immune system (2)(3)(4)(5).…”
Section: A Moebiasis Is a Parasitic Infection Of The Human Intestine mentioning
confidence: 99%
“…DPD down-regulation leads to the disruption of normal pyrimidine metabolism. Additionally, DPD is a crucial enzyme for the growth and survival of the parasite under a glucose-limited environment36. Our previous study showed that the carbohydrate content of B. odoriphaga declines after benzothiazole treatment for 6 h14.…”
Section: Discussionmentioning
confidence: 97%
“…Dihydropyrimidine dehydrogenase (DPD) is the initial and rate-limiting enzyme in the pyrimidine catabolic pathway, in which thymine and uracil are converted into β-alanine or β-aminoisobutyrate using the cofactors NADH or NADPH3536. β-alanine is involved in many metabolic pathways and neurotransmitter functions37.…”
Section: Discussionmentioning
confidence: 99%